Time goes by so slowly (for those who wait): A field experiment in health care - Sofía Garrido; Emilio Gutiérrez (Latin American Economic Review, 2019)
We exploit a unique field experiment to recover the willingness to pay (WTP) for shorter waiting times at a cataract detection clinic in Mexico City, and compare the results with those obtained through a hypothetical dichotomous choice questionnaire. The WTP to avoid a minute of wait obtained from the field experiment ranges from 0.59 to 0.82 Mexican pesos (1 USD = 12.5 Mexican pesos at the time of the survey), while that from the hypothetical choice experiment ranges from 0.33 to 0.48 Mexican pesos. WTP to avoid the wait is lower for lower income individuals, and it is larger the more accurately the announced expected waiting time matches the true values. Finally, we find evidence that the marginal disutility of waiting is not constant.
Keywords: I14; I18; I19; 330; Zahlungsbereitschaftsanalyse; Wartezeit; Gesundheitsvorsorge; Krankenhaus; Mexiko-Stadt; Mexiko